Performance Optimization of SiO2f/SiO2 Composites Derived from Polysiloxane Ceramic Precursors - Xia Zhang; Bo Xiao; Yongzhao Hou; Guangwu Wen (Molecules)
In this paper, polymethylhydrosiloxane (PMHS) and ethanol were used as raw materials to synthesize the ceramic precursor of side ethoxy polysiloxane (PESO) using dehydration and a dealcoholization reaction, which had a ceramic yield of 87.15% and a very low residual carbon content. With the quartz fiber as a reinforcer, the silica matrix composites (SiO2f/SiO2) with a double-layer interface (PyC-SiO2/BNNSs) coating were manufactured using precursor impregnation pyrolysis (PIP). The as-prepared SiO2f/SiO2 possessed an excellent mechanical property, which exhibited obvious fiber pull-out and debonding phenomena from a fracture morphology. The flexural strength and fracture toughness of SiO2f/SiO2 reached 63.3 MPa and 2.52 MPa·m1/2, respectively. Moreover, the SiO2f/SiO2 had suitable dielectric properties, with a dielectric constant of about 2.5 and a dielectric loss of less than 0.01. This work provides an important concept for the enhancement of the dielectric properties and mechanical properties of quartz fiber-reinforced ceramic matrix composites, as well as in the preparation of wave-transmissivity composites.